LEGALITAS ABORSI YANG DILAKUKAN OLEH ANAK AKIBAT PERKOSAAN INSES - Shafira Fatahaya; Rosalia Dika Agustanti (Magister Hukum Universitas Semarang, 2021)
This study aims to examine the legality of abortions performed by children of incest rape victims. Referring to the record of Komnas Perempuan in 2021 there have been cases of incest rape as many as 215 cases where 15 cases occurred in children. From incest rape does not rule out the possibility of pregnancy and physical and psychological unpreparedness that makes the child choose the path to abortion. So that the legality of abortion as Article 75 Paragraph 2 of Law No. 36 of 2009 on Health needs to be questioned if the one who performs the abortion is the child victim of incest rape. Research methods used normative juridical with literature studies. The results showed abortion with indications of rape is legal due to psychological trauma and there may be indications of medical emergencies resulting from incest rape. Abortion can be done at the gestational age of no more than 6 weeks calculated from the beginning of the first period but does not rule out the possibility of abortion when the gestational age exceeds that limit. Law enforcement must be able to ensure that abortions due to incest rape cannot be criminally prosecuted because they have been protected by law because of the existence of legal law. In addition, there is a need for an education about reproductive health by health experts so that abortion cases can be minimized.